Examining barriers and facilitators of dental fear treatment adoption: A qualitative study of practicing dentists - Jennie Ochshorn; Kelly A. Daly; ViniNatalie Zaninovic; Richard E. Heyman; Amy M. Smith Slep; Mark S. Wolff (PLoS ONE, 2025)
Over fifteen percent of the global population experiences dental fear, and although evidence-based treatments exist, adoption of these treatments is almost non-existent. Informed by our prior research examining barriers to adopting face-to-face behavioral treatments in dental operatories, this study examined dentists’ responses to three stepped-care Cognitive Behavioral Therapy for Dental Fear (CBT-DF) formats that use technology. All approaches offer an automated component as the first step (a mobile app) and either an in-person, virtual reality (VR), or video telehealth session as the second step. This study aims to understand which of these approaches would most likely be adopted by private practice dentists and why. Eight focus groups/solo interviews with a total of 13 private practice dentists were conducted with the aim to assess barriers and facilitators to implementing three stepped-care approaches of CBT-DF. The qualitative data obtained from these interviews was coded and analyzed according to Rogers’ framework of innovation (relative advantage, compatibility, complexity, trialability, and observability). The results indicated that participants acknowledged the value of interventions to address dental fear, as they had personal experiences with fearful patients that impacted their practices. Participants responded positively to the automated component of treatment (the app) and were more wary of treatment options requiring office space and staff time (in-person VR and in-person mental health provider). The telehealth option received the most favorable response, although some doubts were expressed regarding relative efficacy and patient accountability. Thus, dissemination of an app-telehealth treatment model that allows dentists to serve as referral partners is promising, given dentists’ incentives to decrease patient fear while avoiding opportunity cost (e.g., occupied chairs and staff time).